Aktivisme Cyber Public Relation Pesantren di Tengah Terpaan Arus Pemberitaan Isu Perundungan Santri - Minan Jauhari (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This article understands the reporting of bullying of students as an issue that affects Islamic educational institutions, especially Islamic boarding schools. Bearing in mind, the issue of bullying in this virtual space has the potential to create a crisis of public confidence. Moreover, the swift flow of news about bullying is not immediately responded to quickly, it will build a negative perception of the islamic boarding school environment. This is because islamic boarding schools, as part of Islamic educational institutions, have so far gained public trust, namely as centers of Islamic studies, especially in the formation of the character of students. This article intends to place cyber public relations activities as a strategic step for Islamic boarding schools, in dealing with the issue of student bullying. Using a virtual ethnographic approach, this study seeks to explore the reality of bullying reporting as a potential crisis, while also exploring cyber public relations activities that are carried out by utilizing internet technology tools and cyber media, so as to suppress potential crises and instill public trust in Islamic boarding schools.